KONSEP PENDIDIKAN KARAKTER DALAM KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DAN KURIKULUM 2013 PADA MATERI BAHASA INDONESIA TINGKAT SMP DAN SMA - Dede Heri Pramono; Esa Khoiruni Abdiyah; Widdy Rahmah Umar; Yeni Rostikawati (IKIP Siliwangi, 2018)
This article tries to express the concept of character education in Education Unit Level Curriculum (KTSP) and Curriculum 2013 on Indonesian language level of junior high and high school. This research uses descriptive-analysis method. Pillar of character that is focused; (1) religious, (2) environmental care, (3) social care, (4) honest and (5) responsibility. The results showed that at the Education Unit Level Curriculum (KTSP) at the junior high level the character education aspect has an average percentage of 90.42%, while the SMA level is 88.38%. As for the curriculum in 2013, the aspect of character education of junior high school has an average percentage of 95.00% while at the level of SMA 83.22%. These results indicate that character education inculcation is more at the Junior high school.